(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
According to researchers, the term "innovation" was introduced into the scientific vocabulary in the 19th century, implying the migration of components between cultural spaces. Currently, literary sources contain many interpretations of this term, which generally point to innovation as the development of new knowledge, objects, technologies. As an innovation, it is proposed to consider complex changes in the unit of an economic, social or technical and technological device, which is replenished with constants that were not previously present in the phenomenon.